How pervasive are Euro-politics? Effects of EU membership on a new member state - Gerda Falkner (Max-Planck-Institut für Gesellschaftsforschung, 1999)
While the consequences of becoming an EU member state for national policies are usually the core concern of pre-membership debates and of post-accession assessments, studies on the effects of European integration on the political systems of the now fifteen member states have so far been less numerous. Among the new EU members, which are ideal cases for studying domestic accession effects, Austria is a particularly challenging case regarding top-down impact on the national political system. A number of specific precautions were taken in order to protect typical features of the national political system (notably the traditional roles of parliament, Länder and social partners) from being eroded in the multi-level system. The basic research question of this article is whether or not these measures were actually successful. How 'sticky' is the EU upon closer inspection, i.e. how pervasive are its effects on adverse national structures? Can national measures, even at the constitutional level, outweigh specific consequences of participating in Euro-politics? If not, why not? The conclusions distinguish specific Austrian variables from generalisable ones and discuss the findings in the light of the existing literature. – – Während die Auswirkungen einer EU-Mitgliedschaft auf inhaltliche Aspekte nationaler Politik zumeist im Mittelpunkt von Beitrittsfolgenabschätzungen stehen, sind Studien über die Folgen der europäischen Integration für die politischen Systeme der fünfzehn Staaten der Europäischen Union noch weniger zahlreich. Innerhalb der 1995 beigetretenen Länder, an deren Beispiel man die Effekte einer Mitgliedschaft besonders gut studieren kann, stellt Österreich den wohl analytisch spannendsten Fall dar. Es wurde nämlich eine ganze Reihe von Ma ßnahmen getroffen, um erwarteten Konsequenzen für traditionelle innerstaatliche Akteure bzw. Entscheidungsmuster gegenzusteuern. Dies betraf vor allem die Rolle von Parlament, Bundesländern und Sozialpartnern im politischen System. Grundlegendes Anliegen des vorliegenden Beitrags war es daher, zu analysieren, ob sich diese Maßnahmen in der Praxis als zielführend erwiesen haben. Wie 'durchdringend' sind die Charakteristika der EU im europäischen Mehrebenensystem, wie stark ist ihr Einfluß auf gewachsene nationale Strukturen? Können nationale Schritte, selbst auf verfassungsgesetzlicher Ebene, bestimmte Konsequenzen einer EU-Mitgliedschaft unterbinden? Wenn nicht, warum? Die Konklusionen unterscheiden österreichspezifische von verallgemeinerungsfähigen Aspekten und diskutieren die Ergebnisse im Lichte anderer Beiträge.
Keywords: 300